Importance of hand-grip strength as an indicator for predicting the results of competitions of young judokas - Gutierrez-Sanchez, A.; Soria-Dominguez, A.; Perez-Turpin, J. A.; Cortell-Tormo, J. M.; Suarez Llorca, C. (Archives of Budo, 2011)
Background and Study Aim: The optimum hand-grip strength during a judo match has become an important element for judo athletes. The aim of this study was to determine whether hand-grip strength is a relevant indicator of predicting the results of competitions of young judokas. Material and Methods: One hundred two judokas (71 male and 31 female) aged between 15 and 19 years participants of the Junior Championship of Galicia 2008 (Spain) took part in this study. The handgrip strength was measured by digital dynamometer in both hands. All subjects complete questionnaire with information about their weight class, results in competition, gender and lateral dominance hand. Results: Male show statistically significant differences in favor higher weight classes. However, the differences in the female divisions were not statistically significant. Differences in handgrip strength among the different podium placements achieved was statistically different in female (p=0.001) but not in male (p=0.198) Conclusions: The results indicated that grip strength is not an extremely relevant factor to take into account for the specific preparation of a competitor since the only relationship found between both parameters was in the female category.